Editorial board, information for authors, and other front matter - Ricky Telg (Journal of Applied Communications, 2013)
This content includes the front cover, the table of contents, editorial and other information for authors for vol. 97, no. 4 (2013) of Journal of Applied Communications
Keywords: masthead